Endovascular Treatment of Late Aortic Perforation due to Vena Cava Filter - Yoshida, Ricardo de Alvarenga [UNESP]; Yoshida, Winston Bonetti [UNESP]; Kolvenbach, Ralf; Bahdur Vieira, Paulo Roberto [UNESP] (Elsevier B.V., 2012)
Perforation of inferior vena cava (IVC) by filter struts ranges from 9% to 24%, and clinical sequelae and complications are unpredictable. The aim of this article was to report an unusual case of late complication of IVC filter that caused an IVC wall perforation and penetration of the filter's hooks in the aorta, which was treated by endovascular procedure. Molding strut tip by balloon angioplasty, its accommodation with a bare stent, and its coverage and protection with an endoprosthesis is probably the first technique reported so far in this situation.